Development of arm movement notification system - Mohd Hazrul, Mohd Rusli (2007)
Cybernetics is a study of communication and control concept related to living organisms with machines. The essential goal of cybernetics is to understand and define the functions and processes of systems (biology). In this project, it will be focus on creating significant signals for respective biology motions of human arm. The application in the future will be the real time adaptation movement of biology human arm towards a mechanical arm. To achieve this goal, an arm movement notification system is developed. This system consists of 2 parts. Firstly the mechanical arm-glove where it will be the sensor that will produce the significant signals for each specific movements made by the human arm. Secondly, a microcontroller system where the significant signal inputs from the arm-glove will be process, identify and show the types of movement on the LCD display which is the degrees position of the human-arm.